PVDF-based composite film and preparation method thereof
By introducing chlorinated alkanes into PVDF and using their molecular interaction with polyvinylidene fluoride to induce conformational self-assembly of the β crystal phase, the problem that PVDF is difficult to obtain high β crystal phase in traditional methods is solved, and high Improved piezoelectric output performance and material stability, suitable for industrial applications.
Patent Information
- Application Number
- CN202411480386.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional PVDF preparation methods are difficult to obtain high-content β crystal phase, which limits the improvement of its piezoelectric properties. In addition, there are problems such as poor compatibility, increased density, and decreased flexibility in addition, which affects the stability of the material and industrial application.
The mass ratio of chlorinated alkanes and polyvinylidene fluoride is 1:1 to 3, and the miscibility is caused by heating and stirring at high temperature, thereby induced conformational self-assembly of non-polar units of fluoropolymer to the polar phase, thereby improving the PVDF PVDF matrix composite film was prepared by β crystal phase content.
It can exhibit high β crystal phase without the need for traditional polarization, improve piezoelectric output performance, improve material stability and reliability, simplify processes, reduce costs, and is suitable for large-scale industrial production, avoiding the disadvantages brought by inorganic substances.
Smart Images

Figure CN119119537A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric film materials, and in particular to a PVDF-based composite film and a preparation method thereof. Background Art
[0002] Polyvinylidene fluoride (PVDF) is a polymer material with excellent piezoelectric properties and is widely used in sensors, actuators, energy harvesters and other fields. Compared with traditional quartz crystals and ferroelectric ceramics, PVDF has significant advantages such as low density, good flexibility, high mechanical strength, low dielectric loss, easy acoustic impedance matching, wide frequency response range, and resistance to chemical and oily corrosion. In addition, PVDF film can also be processed into large areas and complex shapes, which is convenient for various application requirements. The energy storage performance of PVDF is closely related to its crystal structure. Studies have shown that only polar β crystals (serrated) have high piezoelectricity. The performance of PVDF smart materials is mainly determined by the preferentially oriented all-trans (TTTT) dipole (i.e., β phase conformation). However, the β crystal phase content in PVDF is usually low and difficult to exist stably. The insufficient β crystal phase content leads to poor anisotropy and difficulty in orientation polarization of the material, which limits its application as a functional material. In addition, insufficient β-phase content also leads to poor hydrophilicity and permeability of PVDF products, which has become the main bottleneck for the large-scale commercial application of PVDF smart materials. Therefore, whether from the perspective of basic research or market demand, increasing the content of β-phase in PVDF is of great significance to solving the problems in its processing and use.
[0003] The traditional preparation method of PVDF is difficult to obtain a high content of β phase, which limits the further improvement of its piezoelectric properties. In order to increase the β phase content of PVDF, researchers have tried a variety of methods, including adding some inorganic substances. However, these methods have some disadvantages: in the process of making piezoelectric films using polyvinylidene fluoride (PVDF), although the addition of inorganic substances can enhance its piezoelectric properties, there are some significant limitations. First, the compatibility of inorganic substances with PVDF is generally poor, which may lead to uneven microstructure of the material and affect the stability and reliability of the sensor. Secondly, the addition of inorganic substances may increase the density and hardness of the material, thereby reducing the flexibility of PVDF, which is a disadvantage for sensor applications that require flexibility. In addition, the introduction of inorganic substances may increase production costs, and due to the complex processing and dispersion process of inorganic substances, the requirements for process control are high. Environmental factors cannot be ignored. Inorganic substances may contain harmful elements, posing potential risks to the environment and human health. The addition of inorganic substances may affect the long-term durability of PVDF, because inorganic fillers may gradually fall off from the PVDF matrix under mechanical stress or environmental factors, causing the sensor performance to deteriorate over time. Although inorganic substances can improve the piezoelectric properties of PVDF in the short term, from a long-term perspective, the high cost of the synthesis process limits the application of these materials in large-scale industrial production because they are difficult to meet the requirements of cost-effectiveness.
[0004] Therefore, in view of the shortcomings of adding inorganic substances in traditional methods, researchers are exploring new and more effective ways to increase the β-phase content of PVDF. Summary of the invention
[0005] In order to solve the above technical problems, an embodiment of the present invention provides a PVDF-based composite membrane and a preparation method thereof.
[0006] To achieve the above object, the embodiments of the present invention adopt the following technical solutions:
[0007] In one aspect, the present invention provides a PVDF-based composite membrane, comprising chloroalkane and polyvinylidene fluoride, wherein the mass ratio of the chloroalkane to the polyvinylidene fluoride is 1:1-3.
[0008] In some embodiments, the chlorinated alkane includes at least one of 2,5-dichloro-2,5-dimethylhexane, 2,5-dichloro-2,5-dimethylheptane, 2,5-dichloro-2,5-dimethyloctane, or 2,5-dichloro-2,5-dimethylnonane.
[0009] On the other hand, the present invention also provides a method for preparing a PVDF-based composite membrane, comprising the following steps:
[0010] S1, respectively preparing a chloroalkane solution and a polyvinylidene fluoride solution, and mixing them to obtain a mixed solution for standby use;
[0011] S2, placing the S1 mixed solution on a substrate, drying, annealing and cooling to obtain a PVDF-based composite membrane.
[0012] In some embodiments, in S1, the chloroalkane solution is prepared by the following method: dissolving the chloroalkane in an organic solvent and stirring at 60-80° C. for 2-3 h;
[0013] The polyvinylidene fluoride solution is prepared by the following method: polyvinylidene fluoride powder is dissolved in an organic solvent, and stirred at 60-80° C. for 6-8 hours.
[0014] In some embodiments, the organic solvent is N,N-dimethylformamide.
[0015] In some embodiments, in S1, the concentration of the chloroalkane solution is 50 to 150 mg / mL, and the concentration of the polyvinylidene fluoride solution is 150 to 300 mg / mL;
[0016] Furthermore, the temperature of the chloroalkane solution and the polyvinylidene fluoride solution when mixed is controlled at 60-80° C., and stirred for 1-2 hours.
[0017] In some embodiments, in S2, the substrate is a glass plate.
[0018] In some embodiments, in S2, the drying temperature is 60-80°C and the time is 2-3h;
[0019] Furthermore, the annealing temperature is 100-120° C., and the annealing time is 8-10 hours.
[0020] In another aspect, the present invention also provides a method for increasing the β-crystalline content of PVDF, the method comprising: introducing chloroalkane into PVDF to prepare the PVDF-based composite membrane; wherein the mass ratio of the PVDF to the chloroalkane is 1:1-3.
[0021] In some embodiments, a method for increasing the β-crystalline content of PVDF is provided, the method comprising:
[0022] S1, respectively preparing a chloroalkane solution and a polyvinylidene fluoride solution, and mixing them to obtain a mixed solution for standby use;
[0023] S2, placing the S1 mixed solution on a substrate, drying, annealing and cooling to obtain a PVDF-based composite membrane.
[0024] The beneficial effects of the present invention are:
[0025] 1. The present invention uses polyvinylidene fluoride (PVDF) and chloroalkane as raw materials, heats and stirs them at high temperature to make them miscible, utilizes the intermolecular interaction between chloroalkane and polyvinylidene fluoride (PVDF), induces the conformational self-assembly of non-polar units of fluorine-containing polymers into polar phases on the heterogeneous interface, introduces a large number of small and numerous sub-nanometer polar pore interfaces, and effectively increases the β-phase content of PVDF.
[0026] 2. The PVDF-based composite membrane prepared by the present invention can exhibit a high β crystal phase without undergoing a traditional polarization process, thereby directly having excellent piezoelectric output performance.
[0027] 3. By improving the microstructure of the material, the PVDF-based composite membrane of the present invention may have better stability and reliability, which is crucial for long-term applications.
[0028] 4. In addition, due to the simplification of the preparation process and the reduction of costs, this film is easier to achieve large-scale production and meet the large-scale needs of industrial applications. At the same time, it avoids the problems of poor compatibility, increased density, and decreased flexibility caused by inorganic substances.
[0029] 5. The PVDF-based composite membrane prepared by the present invention was tested at an excitation frequency of 1 Hz and a force of 5 N, with a size of 1.5×1.5 cm 2 Piezoelectric performance test: the maximum voltage reaches 27.34V. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the PVDF-based composite membrane E1 prepared in Example 1 of the present invention;
[0031] Figure 2 XRD patterns of the PVDF-based composite membrane E1 prepared in Example 1 of the present invention, the PVDF-based composite membrane E2 prepared in Example 2, the PVDF-based composite membrane E3 prepared in Example 3, and the PVDF-based composite membrane H prepared in Comparative Example 1;
[0032] Figure 3 This is a voltage output diagram of the PVDF-based composite membrane E1 prepared in Example 1 of the present invention under different forces;
[0033] Figure 4 The open circuit voltage graphs of the PVDF-based composite membrane E1 prepared in Example 1 of the present invention, the PVDF-based composite membrane E2 prepared in Example 2, the PVDF-based composite membrane E3 prepared in Example 3, the PVDF-based composite membrane E4 prepared in Example 4, and the PVDF-based composite membrane H prepared in Comparative Example 1 were measured at an excitation frequency of 1 Hz and a force of 5 N;
[0034] Figure 5This is a schematic diagram of the durability test of the PVDF-based composite membrane E1 prepared in Example 1 of the present invention;
[0035] Figure 6 This is a comparison diagram of a PVDF solution containing chlorinated alkane in any embodiment of the present invention and a PVDF solution containing inorganic barium titanate;
[0036] Figure 7 It is a curve of elongation at break of the PVDF-based composite membrane E1 prepared in Example 1 of the present invention and the PVDF-based composite membrane E6 prepared in Comparative Example 2. DETAILED DESCRIPTION
[0037] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.
[0038] PVDF has significant advantages such as low density, good flexibility, high mechanical strength, low dielectric loss, easy acoustic impedance matching, wide frequency response range, and resistance to chemical and oily corrosion. The traditional PVDF preparation method makes it difficult to obtain a high content of β phase, which limits the further improvement of its piezoelectric properties.
[0039] In order to solve the above problems, on the one hand, the embodiments of the present application provide a PVDF-based composite membrane, including chloroalkane and polyvinylidene fluoride, the mass ratio of chloroalkane to polyvinylidene fluoride is 1:1 to 3, illustratively, the mass ratio of chloroalkane to polyvinylidene fluoride can be 1:1, 1:1.5, 1:2, 1:3, the following embodiments are only explained with the mass ratio of chloroalkane to polyvinylidene fluoride being 1:2, and the embodiments of the present application are not specifically limited to this.
[0040] In some embodiments, the chlorinated alkane may include at least one of 2,5-dichloro-2,5-dimethylhexane, 2,5-dichloro-2,5-dimethylheptane, 2,5-dichloro-2,5-dimethyloctane and 2,5-dichloro-2,5-dimethylnonane. For example, the chlorinated alkane may be 2,5-dichloro-2,5-dimethylhexane, 2,5-dichloro-2,5-dimethylheptane, 2,5-dichloro-2,5-dimethyloctane and 2,5-dichloro-2,5-dimethylnonane. Any one of octane, 2,5-dichloro-2,5-dimethylnonane, or the chlorinated alkane can be any two, three or four of 2,5-dichloro-2,5-dimethylhexane, 2,5-dichloro-2,5-dimethylheptane, 2,5-dichloro-2,5-dimethyloctane, and 2,5-dichloro-2,5-dimethylnonane. Any two, three or four of them can be used in any proportion, and this embodiment of the present application does not specifically limit this.
[0041] On the other hand, the present invention also provides a method for preparing a PVDF-based composite membrane, comprising the following steps:
[0042] S1, respectively preparing a chloroalkane solution and a polyvinylidene fluoride solution, and mixing them to obtain a mixed solution for standby use, that is, dissolving the chloroalkane and the polyvinylidene fluoride in corresponding solvents to form a solution so as to be mixed together;
[0043] S2, placing the S1 mixed solution on a substrate, drying, annealing and cooling to obtain a PVDF-based composite membrane.
[0044] In some embodiments, in S1, the chloroalkane solution is prepared by the following method: dissolving the chloroalkane in an organic solvent and stirring at 60-80°C for 2-3h. For example, the stirring temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, and the stirring time can be 2h, 2.2h, 2.5h, 2.8h, 3h. The stirring temperature and time can be adjusted according to the actual dissolution of the chloroalkane, and this embodiment of the present application is not specifically limited to this.
[0045] The polyvinylidene fluoride solution is prepared by the following method: dissolving polyvinylidene fluoride powder in an organic solvent and stirring at 60-80°C for 6-8h. For example, the stirring temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, and the stirring time can be 6h, 6.2h, 6.5h, 7h, 7.5h, 7.8h, 3h. The stirring temperature and time can be adjusted according to the actual dissolution of polyvinylidene fluoride, and this embodiment of the present application is not specifically limited to this.
[0046] In some embodiments, the organic solvent is N,N-dimethylformamide.
[0047] In some embodiments, in S1, the concentration of the chloroalkane solution is 50-150 mg / mL. For example, the concentration of the chloroalkane solution can be 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL, 100 mg / mL, 110 mg / mL, 120 mg / mL, 130 mg / mL, 140 mg / mL, 150 mg / mL, which is not specifically limited to this embodiment of the present application. The concentration of the polyvinylidene fluoride solution is 150-300 mg / mL. Exemplarily, the concentration of the polyvinylidene fluoride solution is 150 mg / mL, 160 mg / mL, 170 mg / mL, 180 mg / mL, 190 mg / mL, 200 mg / mL, 210 mg / mL, 220 mg / mL, 230 mg / mL, 240 mg / mL, 250 mg / mL, 260 mg / mL, 270 mg / mL, 280 mg / mL, 290 mg / mL, and 300 mg / mL, which is not specifically limited to the embodiments of the present application.
[0048] Further, the temperature of the chloroalkane solution and the polyvinylidene fluoride solution when mixed is controlled at 60 to 80°C, and stirred for 1 to 2 hours. Exemplarily, the stirring temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, and the stirring time can be 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours. The stirring temperature and time can be adjusted according to the mixing of the chloroalkane solution and the polyvinylidene fluoride solution, and this embodiment of the application is not specifically limited to this.
[0049] In some embodiments, in S2, the substrate is selected from a glass plate, and any existing common optical glass sheet can be used, and this embodiment of the present application does not specifically limit this.
[0050] In some embodiments, in S2, the drying temperature is 60-80°C, and the time is 2-3h; illustratively, the drying temperature can be 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, and the time can be 2h, 2.1h, 2.2h, 2.3h, 2.5h, 2.8h, 3h, which is not specifically limited to this embodiment of the present application.
[0051] Further, the annealing temperature is 100-120°C, and the time is 8-10h. For example, the annealing temperature can be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 116°C, 118°C, 120°C, and the time is 8h, 8.2h, 8.4h, 8.6h, 8.8h, 9h, 9.2h, 9.4h, 9.6h, 9.8h, 10h. The embodiments of the present application are not specifically limited to this.
[0052] On the other hand, the present invention also provides a method for increasing the β-crystalline phase content of PVDF, the method being: introducing chloroalkanes into PVDF to prepare a PVDF-based composite membrane; wherein the mass ratio of PVDF to chloroalkanes is 1:1-3, and illustratively, the mass ratio of chloroalkanes to polyvinylidene fluoride can be 1:1, 1:1.5, 1:2, 1:3, which is not specifically limited in the embodiments of the present application.
[0053] In some embodiments, a method for increasing the β-crystalline content of PVDF is as follows:
[0054] S1, respectively preparing a chloroalkane solution and a polyvinylidene fluoride solution, and mixing them to obtain a mixed solution for standby use;
[0055] S2, placing the S1 mixed solution on a substrate, drying, annealing and cooling to obtain a PVDF-based composite membrane.
[0056] In order to objectively evaluate the technical effects of the embodiments of the present disclosure, the technical solutions provided by the present disclosure will be described in detail and exemplarily through experimental examples below.
[0057] In order to make the present application easier to understand, the present invention will be described in detail below with reference to embodiments. These embodiments are only for illustration and are not intended to limit the application scope of the present invention.
[0058] Unless otherwise specified, the operations and processing methods involved in this application are conventional methods in the art.
[0059] Unless otherwise specified, the instruments used in this application are conventional instruments in the art.
[0060] Example 1
[0061] S1, dissolve 0.5 g of 2,5-dichloro-2,5-dimethylhexane in 5 mL of N,N-dimethylformamide (DMF), stir magnetically at 60° C. for 3 h, and mix well to obtain material A1 with a concentration of 100 mg / mL;
[0062] S2, dissolving 1 g of polyvinylidene fluoride (PVDF) powder in 5 mL of N,N-dimethylformamide (DMF) solution, stirring magnetically at 80° C. for 8 h to uniformly mix to obtain material B1, the solution concentration being 200 mg / mL;
[0063] S3, mixing the material A1 obtained in S1 with the material B1 obtained in step S2 and magnetically stirring at 60° C. for 2 h to obtain material C1;
[0064] S4, take 5 mL of S3 to obtain the mixed solution of material C1, spray it on a 5 cm × 5 cm clean glass plate, and heat it at 60 ° C for 3 h to obtain material D1;
[0065] S5, annealing the material D1 obtained in S4 at 120°C in a vacuum oven for 8 hours, fully removing the DMF solvent while the high temperature is also conducive to the crystal growth of the PVDF film. Then slowly cool the annealed film to room temperature to obtain a high β-crystalline PVDF-based composite film E1.
[0066] The PVDF-based composite membrane E1 was packaged, and then the performance of the PVDF-based composite membrane E1 obtained by S5 was tested using a signal generator, a power amplifier, an exciter and a Keithley 6514 electrometer.
[0067] pass Figure 1 It can be seen that the addition of 2,5-dichloro-2,5-dimethylhexane in Example 1 forms a porous structure in the PVDF-based composite membrane E1. The following Table 1 shows the voltage output of the PVDF-based composite membrane E1 under different forces. Figure 3 It can be seen that the voltage output of PVDF-based composite membrane E1 under a force of 5N is stable.
[0068] Table 1
[0069] Example materials Frequency Hz Force N Output voltage V 1 PVDF-based composite membrane E1 1Hz 1N 15.52V 1 PVDF-based composite membrane E1 1Hz 2N 20.68V 1 PVDF-based composite membrane E1 1Hz 4N 24.68V 1 PVDF-based composite membrane E1 1Hz 5N 27.34V 1 PVDF-based composite membrane E1 1Hz 6N 31.08V 1 PVDF-based composite membrane E1 1Hz 7N 32.41V 1 PVDF-based composite membrane E1 1Hz 8N 33.27V 1 PVDF-based composite membrane E1 1Hz 9N 35.39V 1 PVDF-based composite membrane E1 1Hz 9N 35.89V
[0070] It can be seen from Table 1 above that when the external force increases from 1N to 9N, the output voltage of the piezoelectric sensor gradually increases.
[0071] Example 2
[0072] S1, dissolve 0.5 g of 2,5-dichloro-2,5-dimethylheptane in 5 mL of N,N-dimethylformamide (DMF), stir magnetically at 60° C. for 3 h, and mix well to obtain material A2 with a concentration of 100 mg / mL;
[0073] S2, dissolving 1 g of polyvinylidene fluoride (PVDF) powder in 5 mL of N,N-dimethylformamide (DMF) solution, stirring magnetically at 80°C for 8 h to uniformly mix to obtain material B2, the solution concentration is 200 mg / mL;
[0074] S3, mixing the material A2 obtained in S1 with the material B2 obtained in S2 and magnetically stirring at 60° C. for 2 h to obtain material C2;
[0075] S4, take 5ml S3 to obtain the mixed solution of material C2, spray it on a 5cm×5cm clean glass plate, and heat it at 60℃ for 3h to obtain material D2;
[0076] S5, annealing the material D2 obtained in S4 at 120°C in a vacuum oven for 8 hours, fully removing the DMF solvent while the high temperature is also conducive to the crystal growth of the PVDF film. Then slowly cool the annealed film to room temperature to obtain a high β-crystalline PVDF-based composite film E2.
[0077] The PVDF-based composite membrane E2 was packaged, and then the performance of the PVDF-based composite membrane E2 obtained in S5 was tested using a signal generator, a power amplifier, an exciter and a Keithley 6514 electrometer.
[0078] Example 3
[0079] S1, dissolve 0.5 g of 2,5-dichloro-2,5-dimethyloctane in 5 mL of N,N-dimethylformamide (DMF), stir magnetically at 60° C. for 3 h, and mix well to obtain material A3 with a concentration of 100 mg / mL;
[0080] S2, dissolving 1 g of polyvinylidene fluoride (PVDF) powder in 5 mL of N,N-dimethylformamide (DMF) solution, stirring magnetically at 80°C for 6 h to uniformly mix to obtain material B3, the solution concentration is 200 mg / mL;
[0081] S3, mixing the material A3 obtained in S1 with the material B3 obtained in S2 and magnetically stirring at 60° C. for 2 h to obtain material C3;
[0082] S4, take 5ml S3 to obtain the mixed solution of material C3, spray it on a 5cm×5cm clean glass plate, and heat it at 60℃ for 3h to obtain material D3;
[0083] S5, annealing the material D3 obtained in S4 at 120°C in a vacuum oven for 8 hours, fully removing the DMF solvent while the high temperature is also conducive to the crystal growth of the PVDF film. Then slowly cool the annealed film to room temperature to obtain a PVDF-based composite film E3 with a high β crystal phase.
[0084] The PVDF-based composite membrane E3 was packaged, and then the performance of the PVDF-based composite membrane E3 obtained by S5 was tested using a signal generator, a power amplifier, an exciter and a Keithley 6514 electrometer.
[0085] Example 4
[0086] S1. Dissolve 0.5 g of 2,5-dichloro-2,5-dimethylnonane in 5 mL of N,N-dimethylformamide (DMF), stir under magnetic stirring at 60° C. for 3 h, and mix well to obtain material A4 with a concentration of 100 mg / mL.
[0087] S2, dissolving 1 g of polyvinylidene fluoride (PVDF) powder in 5 mL of N,N-dimethylformamide (DMF) solution, stirring magnetically at 80° C. for 6 h to uniformly mix to obtain material B4, the solution concentration being 200 mg / mL;
[0088] S3, mixing the material A4 obtained in S1 with the material B4 obtained in S2 and magnetically stirring at 60° C. for 2 h to obtain material C4;
[0089] S4, take 5ml S3 to obtain the mixed solution of material C4, spray it on a 5cm×5cm clean glass plate, and heat it at 60℃ for 3h to obtain material D4;
[0090] S5, annealing the material D4 obtained in S4 at 120°C in a vacuum oven for 8 hours, fully removing the DMF solvent while the high temperature is also conducive to the crystal growth of the PVDF film. Then slowly cool the annealed film to room temperature to obtain a PVDF-based composite film E4 with a high β crystal phase.
[0091] The PVDF-based composite membrane E4 was packaged, and then the performance of the PVDF-based composite membrane E4 obtained by S5 was tested using a signal generator, a power amplifier, an exciter and a Keithley 6514 electrometer.
[0092] Example 5
[0093] S1, 0.3 g of 2,5-dichloro-2,5-dimethylhexane and 0.2 g of 2,5-dichloro-2,5-dimethylheptane were dissolved in 5 mL of N,N-dimethylformamide (DMF), mixed, and magnetically stirred at 60° C. for 3 h. The mixture was uniformly mixed to obtain material A5 with a concentration of 100 mg / mL;
[0094] S2, dissolving 1 g of polyvinylidene fluoride (PVDF) powder in 5 mL of N,N-dimethylformamide (DMF) solution, stirring magnetically at 80° C. for 8 h to uniformly mix to obtain material B5, the solution concentration being 200 mg / mL;
[0095] S3, mixing the material A5 obtained in S1 with the material B5 obtained in step S2 and magnetically stirring at 60° C. for 2 h to obtain material C5;
[0096] S4, take 5 mL of S3 to obtain the mixed solution of material C5, spray it on a 5 cm × 5 cm clean glass plate, and heat it at 60 ° C for 3 h to obtain material D5;
[0097] S5, annealing the material D5 obtained in S4 at 120°C in a vacuum oven for 8 hours, fully removing the DMF solvent while the high temperature is also conducive to the crystal growth of the PVDF film. Then slowly cool the annealed film to room temperature to obtain a PVDF-based composite film E5 with a high β crystal phase.
[0098] The PVDF-based composite membrane E5 was packaged, and then the performance of the PVDF-based composite membrane E5 obtained by S5 was tested using a signal generator, a power amplifier, an exciter and a Keithley6514 electrometer.
[0099] Comparative Example 1
[0100] S1. Dissolve 1 g of polyvinylidene fluoride (PVDF) powder in 10 mL of N,N-dimethylformamide (DMF) solution, and stir magnetically at 80°C for 6 h to uniformly mix to obtain material F, with a solution concentration of 100 mg / mL;
[0101] S2, take 5 ml of the material F obtained by S1 and spray it on a 5 cm × 5 cm clean glass plate, and heat it at 60 ° C for 3 h to obtain material G;
[0102] S3. The material G obtained in S3 is annealed in a vacuum oven at 120° C. for 8 h to fully remove the DMF solvent, and then the annealed film is slowly cooled to room temperature to obtain a PVDF-based composite film H without adding chloroalkane.
[0103] The PVDF-based composite membrane H was packaged, and then the performance of the PVDF-based composite membrane H obtained in S5 was tested using a signal generator, a power amplifier, an exciter and a Keithley 6514 electrometer.
[0104] Comparative Example 2
[0105] S1. Dissolve 3 g of 2,5-dichloro-2,5-dimethylhexane in 5 mL of N,N-dimethylformamide (DMF), stir the mixture under magnetic stirring at 60° C. for 3 h, and mix well to obtain material A6 with a concentration of 100 mg / mL.
[0106] S2, dissolving 1 g of polyvinylidene fluoride (PVDF) powder in 5 mL of N,N-dimethylformamide (DMF) solution, stirring magnetically at 80° C. for 8 h to uniformly mix to obtain material B6, with a solution concentration of 200 mg / mL;
[0107] S3, mixing the material A6 obtained in S1 with the material B1 obtained in step S2 and magnetically stirring at 60° C. for 2 h to obtain material C6;
[0108] S4, take 5 mL of S3 to obtain the mixed solution of material C6, spray it on a 5 cm × 5 cm clean glass plate, and heat it at 60 ° C for 3 h to obtain material D6;
[0109] S5, annealing the material D6 obtained in S4 at 120°C in a vacuum oven for 8 hours, fully removing the DMF solvent while the high temperature is also conducive to the crystal growth of the PVDF film. Then slowly cool the annealed film to room temperature to obtain a high β-crystalline PVDF-based composite film E6.
[0110] Figure 2 XRD patterns of PVDF-based composite membrane E1 prepared in Example 1 of the present invention, PVDF-based composite membrane E2 prepared in Example 2, PVDF-based composite membrane E3 prepared in Example 3, and PVDF-based composite membrane H prepared in Comparative Example 1. In PVDF, the 20.6° crystallization peak represents the β phase, which corresponds to the (200) and (110) crystal plane reflections. Figure 2 It can be seen that the 20.6° crystallization peak representing the β phase in the PVDF film without adding chlorinated alkanes is significantly increased in the PVDF fiber compared to the PVDF film with added chlorinated alkanes. This shows that adding chlorinated alkanes is beneficial to increasing the β crystal content of the PVDF film. Table 2 below shows the maximum voltage values measured at an excitation frequency of 1 Hz and a force of 5 N for the PVDF-based composite membrane E1 prepared in Example 1, the PVDF-based composite membrane E2 prepared in Example 2, the PVDF-based composite membrane E3 prepared in Example 3, the PVDF-based composite membrane E4 prepared in Example 4, and the PVDF-based composite membrane H prepared in Comparative Example 1.
[0111] Table 2
[0112] Example materials Frequency Hz Force N Output voltage V Example 1 PVDF-based composite membrane E1 1Hz 5N 27.34V Example 2 PVDF-based composite membrane E2 1Hz 5N 18.52V Example 3 PVDF-based composite membrane E3 1Hz 5N 16.47V Example 4 PVDF-based composite membrane E4 1Hz 5N 12.36V Comparative Example 1 PVDF-based composite membrane H 1Hz 5N 0.5V
[0113] pass Figure 4 It can be seen that the PVDF-based composite membrane E1 prepared in Example 1, the PVDF-based composite membrane E2 prepared in Example 2, the PVDF-based composite membrane E3 prepared in Example 3, and the PVDF-based composite membrane E4 prepared in Example 4 all have stable voltage output under an excitation frequency of 1 Hz and a force of 5 N. The PVDF-based composite membrane H prepared in Comparative Example 1 has a low output voltage because the film is destroyed due to the addition of excessive chlorinated alkanes.
[0114] pass Figure 5 It can be seen that the output signal of the PVDF-based composite membrane E1 prepared in Example 1 in the PVDF pressure sensor does not drop significantly after 30,000 cycles, and still has good stability. For a clearer observation, the enlarged views extracted from the data of 20 cycles, 15,000 cycles, and 30,000 cycles respectively show that these waveforms remain consistent. This shows that the device can meet the requirements of stable response.
[0115] That is, through Figure 5 As shown in the figure, durability tests were carried out at an operating frequency of 1 Hz to evaluate its stability under cyclic pressure. Figure 5As shown, the results show that a stable signal that does not weaken after 30,000 cycles is continuously generated from the insets of the start curve and the end curve, and the insets show the enlarged early, middle and late signals. Therefore, these experiments show that the prepared pressure sensor has good reliability and mechanical durability, clarifying its practical value.
[0116] pass Figure 6 It can be seen that the PVDF solution with chloroalkanes added is transparent, while the PVDF solution with the inorganic BaTiO3 (barium titanate) added is white and opaque, which shows that the chloroalkanes have good compatibility with PVDF and can be evenly dispersed without significantly changing the original properties of PVDF. When the inorganic BaTiO3 is added to the PVDF solution, the solution becomes opaque. This is because the compatibility of BaTiO3 and PVDF is poor, resulting in uneven dispersion of BaTiO3 particles in the PVDF matrix, forming larger particles or aggregates, thereby affecting the transparency of the solution. That is, the present invention avoids the problems of poor compatibility, increased density, decreased flexibility, etc. caused by inorganic substances.
[0117] pass Figure 7 It can be seen that the PVDF-based composite membrane E1 prepared in Example 1, which added a suitable amount of chlorinated alkanes, had an elongation at break of 16%, while the PVDF-based composite membrane E6 prepared in Comparative Example 2 had an elongation at break of 2% due to the addition of excessive chlorinated alkanes. It can be seen that the excessive addition of chlorinated alkanes caused the deterioration of the mechanical properties of the film, which was manifested as increased brittleness and reduced ductility.
[0118] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.
[0119] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A PVDF-based composite membrane, characterized in that: The raw materials of the composite membrane include chloroalkane and polyvinylidene fluoride, and the mass ratio of the chloroalkane to the polyvinylidene fluoride is 1:1-3.
2. A PVDF-based composite membrane according to claim 1, characterized in that: The chloroalkane includes at least one of 2,5-dichloro-2,5-dimethylhexane, 2,5-dichloro-2,5-dimethylheptane, 2,5-dichloro-2,5-dimethyloctane or 2,5-dichloro-2,5-dimethylnonane.
3. The method for preparing a PVDF-based composite membrane according to claim 1 or 2, characterized in that: The following steps are involved: S1, respectively preparing a chloroalkane solution and a polyvinylidene fluoride solution, and mixing them to obtain a mixed solution for standby use; S2, placing the S1 mixed solution on a substrate, drying, annealing and cooling to obtain a PVDF-based composite membrane.
4. The preparation method according to claim 3, characterized in that: In step S1, the chloroalkane solution is prepared by the following method: dissolving the chloroalkane in an organic solvent and stirring at 60-80° C. for 2-3 hours; The polyvinylidene fluoride solution is prepared by the following method: polyvinylidene fluoride powder is dissolved in an organic solvent, and stirred at 60-80° C. for 6-8 hours.
5. The preparation method according to claim 4, characterized in that: The organic solvents are all N,N-dimethylformamide.
6. The preparation method according to claim 4, characterized in that: In step S1, the concentration of the chloroalkane solution is 50-150 mg / mL, and the concentration of the polyvinylidene fluoride solution is 150-300 mg / mL; Furthermore, the temperature of the chloroalkane solution and the polyvinylidene fluoride solution when mixed is controlled at 60-80° C., and stirred for 1-2 hours.
7. The preparation method according to claim 4, characterized in that: In step S2, the substrate is a glass plate.
8. The preparation method according to claim 4, characterized in that: In step S2, the drying temperature is 60-80°C and the drying time is 2-3 hours; Furthermore, the annealing temperature is 100-120° C., and the annealing time is 8-10 hours.
9. A method for increasing the β-crystalline content of PVDF, characterized in that: The method comprises the following steps: introducing chloroalkane into PVDF to prepare a PVDF-based composite membrane; wherein the mass ratio of the PVDF to the chloroalkane is 1:1-3.
10. A method for increasing the β-crystalline content of PVDF according to claim 9, characterized in that: The method is: S1, respectively preparing a chloroalkane solution and a polyvinylidene fluoride solution, and mixing them to obtain a mixed solution for standby use; S2, placing the S1 mixed solution on a substrate, drying, annealing and cooling to obtain a PVDF-based composite membrane.
